Truths : 500 years European Christians in history : war, robbery, murder, genocide, occupation, exploitation : churches, universities, demigods like Max Müller, prepare the ground - Prodosh Aich (Rare Books, 2015)
There are many persons on the paths to gain insights, to acquire knowledge and to get to truths. The contemporary societies do not offer facilities to getting together of these persons. How could they get together? In this particular case, the two authors of this book, both are agonized by the distortions of the cultural heritage of Bharatavarsa, a vast land which has later been named India by foreign people. These deliberate distortions of the cultural heritage of Bharatavarsa have been brought into the world by the foreign occupants and then further cultivated by their local stooges. In the beginning of their getting together the agony of the two authors is at different realms and levels. There are many persons suffering from such agonies. But how could they get together? Both authors are also distressed becoming more and more sensitive on the continuous worsening of the Era of Vasco da Gama, which began by the declaration of a War by the European Christians on the rest of the world in the 15th century. The Vatican sanctioned the Kings of Portugal and Spain to occupy foreign lands and to annex these lands to their kingdoms. This book does not pretend to deal with history. This book deals with our past and with our present by connecting facts that have been disconnected by so-called philosophers, historians, and social scientists in general and by scholars extraordinary in particular. It looks back to ancient heritage based on primary documents and evidences. This book does not intend to describe our past, does not intend to add just another story to the lot, as modern historians do. It simply puts facts coherently together that are based on primary documentary sources. It is a report of a rigorous scrutiny of secondary sources. It puts scholars and their scholarly deliberations to the test of validity collating with the primary documents.